Pemanfaatan Media Komunikasi Dan Informasi Sebagai Pembangunan Nasional - Setiamenda Ginting; Rachel Mia L. Lumbantoruan; Noyanta Luga; Niat Hati Gulo; Stephen Boy Harefa (Universitas Sari Mutiara Indonesia, 2023)
This scientific work is the result of analysis and literature review which reviews communication and information media, namely social media in the form of social networks as a very effective medium used as a communication and information medium to convey people's problems or aspirations, especially for areas that have not been maximally touched by media. This research aims to: first, describe the characteristics of digital era society who use communication media. Second, describe the relationship between communication media and national development and Third, describe the opportunities and challenges that arise in digital era society. And fourth, describe the efforts that must be made in the digital era. This research method is descriptive research with a qualitative approach. Researchers collect data according to existing events. Then the data is analyzed by collecting data, reducing data, presenting the data and then drawing conclusions or verification. The research results show that national development will be realized well if there is communication media in the form of social networks that people use correctly, ethically and responsibly. This can be achieved by the wider community by collaborating between the community and the local government, namely by providing education in all places evenly.